Synthesis and Fungicidal Activity of Hydrazone Derivatives Containing 2(3H)-Benzothiazolone Moiety - Weng, Jian-Quan; Huang, Hua; Yu, Zhi-Qin; Zhang, Hong-Min; Tan, Cheng-Xia; Liu, Xing-Hai (Asian Journal of Chemistry, 2011)
Fifteen novel hydrazone derivatives containing 2(3H)-benzothiazolone moiety were synthesized by condensing 2-oxobenzothiazolin-3-ylacetohydrazide with substituted ketones. Their structures were characterized by 1H NMR, FTIR, MS and elemental analysis. The biological activities of the hydrazone derivatives were investigated. The bioassay results indicated that some of these compounds exhibit excellent fungicidal activities.